Serotype AD Strains of Cryptococcus neoformans Are Diploid or Aneuploid and Are Heterozygous at the Mating-Type Locus - Lengeler, Klaus B. (American Society for Microbiology, 2001)
Cryptococcus neoformans is a pathogenic basidiomycete with a defined sexual cycle involving mating between haploid yeast cells with a transient diploid state. C. neoformans occurs in four predominant serotypes (A, B, C, and D), which represent different varieties or species. Rare clinical and environmental isolates with an unusual AD serotype have been reported and suggested to be diploid. We found by fluorescence-activated cell sorter analysis that serotype AD strains are aneuploid or diploid. PCR analysis with primers specific for serotype A or D alleles of the CNA1, CLA4, and GPA1 genes revealed that both alleles are often present in serotype AD strains. PCR analysis with primers specific for genes in the MATa or MATα mating-type loci revealed that serotype AD strains are heterozygous for the mating-type locus. Interestingly, in several serotype AD strains, the MATα locus was derived from the serotype D parent and the MATa locus was inherited from a serotype A parent that has been thought to be extinct. Basidiospores from a self-fertile serotype AD strain bearing the putative serotype A MATa locus showed a very low viability (∼5%), and no fertile serotype A MATa strain could be recovered. Serotype AD strains were virulent in a murine model. Hybrid AD strains could readily be isolated following a laboratory cross between a serotype A strain and a serotype D strain. In summary, serotype AD strains of C. neoformans are unusual aneuploid or diploid strains that result from matings between serotype A and D strains. Self-fertile isolates fail to undergo normal meiosis because of genetic divergence. Our findings further suggest that serotype A MATa strains may exist in nature.